Narrating Childhood in Elena Chizhova's Vremya zhenshchin. (3rd July 2016) - Sorvari, Marja
ABSTRACT: This article discusses the representation of the Soviet past through the figure of a child in Elena Chizhova's novel Vremja ženščin [Vremya zhenshchin] (2009). The concept of the vulnerable subject is applied to conceptualize the narrative's 'access' to the past. Vremja ženščin [Vremya zhenshchin] tells the story of a mute girl raised by her mother and three 'grandmothers' in 1960s Leningrad. The women decide to keep her muteness as a secret in order to protect her from being sent to a state institution for disabled children, and to raise her at home. The child figure is situated on the verge of two value systems: the collective, secular, and modern value system, represented by the outside world of home; and the private, spiritual, and traditional value system represented by the community of three old women. The position of the vulnerable child figure on the margins of society enables the representation of a 'lost' past and its alternative values. The article suggests that the vulnerable child figure can be seen to stand for a feeling of loss and abandonment in more general terms in contemporary Russia, and as representing a search for a lost inheritance.